P405 Sustainability of biologic therapies is less in UC than CD patients independent of prior biologic experience. (25th January 2019) - Doherty, J; Buckley, M; Cullen, G; Keegan, D; Byrne, K; Horgan, G; Mulcahy, H; Sheridan, J; Doherty, G A
Abstract: Background: Treatment of inflammatory bowel disease (IBD) with biologics is usually effective but may be discontinued due to inadequate response or adverse effects. Few studies have examined what determines sustainability of treatment in a real-world setting. Methods: To determine factors which determine sustainability of biologic therapy we performed a single-centre retrospective study of a prospectively maintained database of 4200 IBD patients. Patients were subdivided on whether they had ulcerative colitis (UC + IBD-U included) or Crohn's disease (CD), whether they were biological-naïve vs. experienced when they received a particular biologic. Our primary endpoint was time to discontinuation of biologic (due to inadequate response or adverse effects) in biologic naïve (Group 1) and biologic experienced patients (Group 2) depending whether they were diagnosed with UC or CD. The impact of immunomodulator co-therapy and other disease characteristics was examined. Results: A total of 765 patients with complete data were included in our analysis. Group 1: 539 patients were in our biologic naïve group. 117 (21.71%) were treated with Infliximab (IFX). 375(69.57%) with adalimumab (ADA). Fifteen (2.78%) were on Vedolizumab (VD). Thirty-two(5.94%) were on golimumab (GB). 192(35.6%) had UC. 347(64.4%) patients have CD. Median time to discontinuation was 2.84 years in UC which was significantly shorter than in CD patients with median time to discontinuation of 3.59 years (p = 0.000) (Table 1, Graph 2).Group 2: 226 patients were in our biologic experienced group. Seventy-nine(35%) were treated with IFX, 53 (23.45%) with ADA, 28(12.4%) with VD. 28(12.4%) were treated with GB, 38 (16.81%) with Ustekinumab (UST). 74(32.74%) had UC. 149(65.93%) had CD. Median time to discontinuation in UC was 2.58 years compared with 3.83 years in CD (p = 0.010) (Table 1, Graph 1). No significant differences in time to biologic discontinuation were observed between biologic naïve and biologic experienced treatments. Conclusions: Our real-world data indicate that the sustainability of biologic treatment is less in UC than in CD patients and is not strongly determined by prior biologic exposure. These findings are important in determining how biologic therapies are employed in both IBD subtypes and suggest the need for new non-biologic/small molecules to demonstrate their relative sustainability as IBD therapies.